Marriage and Divorce: The Role of Labor Market Institutions - Bastian Schulz; Fabian Siuda (Center for Economic Studies and Ifo Institute (CESifo), 2020)
Marriage and divorce decisions are influenced by the institutional environment they are made in. One example is the social insurance system, which acts as a substitute for within-household insurance against economic shocks. In this paper, we quantify the importance of household-level insurance for marriage and divorce by exploiting an exogenous increase in the need for risk sharing: in January 2003, a German labor market reform sharply reduced means-testing exemptions in the unemployment insurance system and thereby increased the extent to which spouses have to insure each other against unemployment. Using social security register data, we show that the extent to which (potential) spouses were affected by this reform varies with nationality. We then follow a differences-in-differences identification strategy and use data on all marriages and divorces in Germany between 1997 and 2013 to show that increased means testing made the formation of interethnic marriages significantly less attractive. At the same time, the reform increased the stability of newly-formed interethnic marriages.
Keywords: J10; J12; J15; J64; J65; 330; marriage; divorce; interethnic marriage; risk sharing; unemployment insurance; labor market reforms; EU expansion